Molecular Basis of the Bohr Effect in Arthropod Hemocyanin - Hirota, Shun (American Society for Biochemistry and Molecular Biology, 2008)
Flash photolysis and K-edge x-ray absorption spectroscopy (XAS) were used to investigate the functional and structural effects of pH on the oxygen affinity of three homologous arthropod hemocyanins (Hcs). Flash photolysis measurements showed that the well-characterized pH dependence of oxygen affinity (Bohr effect) is attributable to changes in the oxygen binding rate constant, k(on), rather than changes in k(off). In parallel, coordination geometry of copper in Hc was evaluated as a function of pH by XAS. It was found that the geometry of copper in the oxygenated protein is unchanged at all pH values investigated, while significant changes were observed for the deoxygenated protein as a function of pH. The interpretation of these changes was based on previously described correlations between spectral lineshape and coordination geometry obtained for model compounds of known structure (Blackburn, N. J., Strange, R. W., Reedijk, J., Volbeda, A., Farooq, A., Karlin, K. D., and Zubieta, J. (1989) Inorg. Chem.,28 ,1349 -1357). A pH-dependent change in the geometry of cuprous copper in the active site of deoxyHc, from pseudotetrahedral toward trigonal was assigned from the observed intensity dependence of the 1s → 4p(z) transition in x-ray absorption near edge structure (XANES) spectra. The structural alteration correlated well with increase in oxygen affinity at alkaline pH determined in flash photolysis experiments. These results suggest that the oxygen binding rate in deoxyHc depends on the coordination geometry of Cu(I) and suggest a structural origin for the Bohr effect in arthropod Hcs.